Characterization and evaluation of potential halotolerant phosphate solubilizing bacteria from Salicornia fruticosa rhizosphere - Teles, E. A. P.; Xavier, J. F.; Arcênio, F. S.; Amaya, R. L.; Gonçalves, J. V. S.; Rouws, L. F. M.; Zonta, E.; Coelho, I. S. (Frontiers in Plant Science, 2024)
Soil salinization is a significant abiotic factor threatening agricultural production, while the low availability of phosphorus (P) in plants is another worldwide limitation. Approximately 95-99% of the P in soil is unavailable to plants. Phosphate-solubilizing bacteria (PSB) transform insoluble phosphates into soluble forms that plants can utilize. The application of PSB can replace or partially reduce the use of P fertilizers. Therefore, selecting bacteria with high solubilization capacity from extreme environments, such as saline soils, becomes crucial. This study aimed to identify twentynine bacterial strains from the rhizosphere of Salicornia fruticosa by sequencing the 16S rDNA gene, evaluate their development in increasing concentrations of NaCl, classify them according to their salinity response, and determine their P solubilization capability. The bacteria were cultivated in nutrient agar medium with NaCl concentrations ranging from 0.5% to 30%. The phosphate solubilization capacity of the bacteria was evaluated in angar and broth National Botanical Research Institute (NBRIP) media supplemented with calcium phosphate (CaHPO4) and aluminum phosphate (AlPO4), and increased with 3% NaCl. All bacterial strains were classified as halotolerant and identified to the genera Bacillus, Enterobacter, Halomonas, Kushneria, Oceanobacillus, Pantoea, Pseudomonas, and Staphylococcus, with only one isolate was not identified. The isolates with the highest ability to solubilize phosphorus from CaHPO 4 in the liquid medium were Kushneria sp. (SS102) and Enterobacter sp. (SS186), with 989.53 and 956.37 mg•Kg -1 P content and final pH of 4.1 and 3.9, respectively. For the solubilization of AlPO 4 , the most effective isolates were Bacillus sp. (SS89) and Oceanobacillus sp. (SS94), which raised soluble P by 61.10 and 45.82 mg•Kg -1 and final pH of 2.9 and 3.6, respectively. These bacteria demonstrated promising results in in vitro P solubilization and can present potential for the development of bioinput. Further analyses, involving different phosphate sources and the composition of produced organic acids, will be conducted to contribute to a comprehensive understanding of their applications in sustainable agriculture.